REVITALISASI SEKOLAH LUAR BIASA (SLB) PASCA IMPLEMENTASI PROGRAM PENDIDIKAN INKLUSI - Slamet Hw; Joko Santosa (Universitas Muhammadiyah Surakarta, 2012)
Inclusion education is the education which incorporates children with special needs to learn with peers in regular schools. Extraordinary School is the one which is organized to serve school-age children with special needs (having a physical or mental disorder). With regards to the implementation of inclusion education, people question about the existence of Extra Ordinary Schools. The problem is how the existence of Extraordinary School after the enactment of Inclusion Education. It is important to investigate this issue. The study was conducted in 12 Extraordinary Schools in four districts of Surakarta. The result indicates that most respondents answered optimistically that Extraordinary Schools will exist, due to various reasons: (1) not all of the staff can be accommodated by the School Inclusion, hearing and mentally disabled children (light, medium) which have a special feature that is his IQ below normal child can no longer be admitted to the class with regular normal children, deaf children have difficulty to attend inclusion class, blind children who have normal average IQs can attend Inclusion School with supervision of Special Teacher, disabled children who have normal IQ most likely to be accepted in the Inclusion School, slowlearning children and children with autism also can be handled by special teacher Inclusion School, (2) The most parents of children with disabilities still entrust their children educated in special schools who have enough experience rather than send their children to Inclusion school, (3) Inclusion Education can be managed in collaboration with Extraordinary School nearby (4) the majority of people, especially young parents do not know about Inclusion School, and (5) the existing Extraordinary School is well established, with adequate infrastructure, has a strong legal basis, and professional teachers. Thus Extraordinary School will remain there despite the existence of Inclusion School.